GROWTH RATESTOCK OF Thynnichthysthynnoides IN THE BUNTER LAKE PANGKALAN BARU VILLAGE SIAK HULU SUP REGENCY KAMPAR REGENCY RIAU PROVINCE - Aisa, Nur; Sumiarsih, Eni; El Fajri, Nur (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Thynnichthysthynnoides is commonly inhabit the Bunter Lake. A research aims to understandthe growth rateof the fish in the Bunter Lake has been conducted in April-May 2019. The method used in this study is a survey method in which the waters of Lake Bunter as a research location. The fish was sampled everyday for24 days, using gillnets. The fish that are taken from the smallest to the largest, which represent each size and weight of the fish.Results shown that theasymptotic length ((L∞) 20.11 mm, growth coefficient (K) 0.74/year, and t0 -0.2426/year. It means that the growth of fish in Lake Bunter takes 6 months to reach an asymptotic length value. Results shown thatthe water quality of the Bunter Lake are as follows temperature 29-30oC, tranparancy40-65 cm, depth1,80-9,10 M, pH 9 and dissolved oxsygen3,8-4,4 mg/L. Water quality in the Bunter Lake is able to support the life of T. thynnoides.    Keywords :Oxbow lake, growth coefficient, water quality,growth, asymptotic length